Research on distributed energy sharing strategies of industrial clusters under consumers’ low-carbon preferences - Haoyan Fu; Li Song (Systems Science & Control Engineering)
Distributed energy sharing is an effective means for enterprises to improve energy utilization efficiency and reduce carbon emissions. With the continuous improvement of consumers' low-carbon awareness, low-carbon preference has an important impact on distributed energy sharing strategies. In this context, we introduce the energy saving benefit sharing contract and use the backward induction method to analyze the optimal equilibrium strategies of distributed energy sharing in industrial clusters. Then we conduct a comparative analysis of the equilibrium results. Finally, the above results are analyzed and verified by numerical simulation. The results show that when the ratio of energy low-carbon cost coefficient is within a certain range, energy sharing with integrated energy service providers is the optimal choice for enterprises in industrial clusters, and the centralized decision is better than the decentralized decision; The higher the consumer's low-carbon preference, the higher the product's low-carbon level and total system profitability; As the energy saving benefit sharing ratio increases, the low carbon level of the product and the profit of the integrated energy service provider also increases, and the total profit of the enterprises first increases and then decreases.